PSYCHO-EMOTIONAL PECULIARITIES OF WORKERS FROM LEGAL FIELD - Melentieva Aliona (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
The activity in legal field is varied, taking into account that this large sphere is related to the defense of fundamental rights and freedom of a person, duet to the responsibility provided, emanated by the workers from justice field, the responsibility to protect fundamental norms in force. Workers of legal, justice field, daily confront situations of infringements of civil, criminal and administrative laws, as well as the violation of procedural-criminal order. In the given study we are going to determine the psycho-emotional peculiarities of specialists from justice/legal field, namely to research the level of manifestation of anxiety, aggressiveness, rigidity and frustration. The sample of the given study is formed by jurists, attorneys, as well as prosecuting officers – the majority of subjects are men with different age and professional experience in the field.